Hierarchical IPv6 Network Design Using SLAAC and DHCPv6 for Enterprise Environments - Attabie, Bushra; Nuredin Ahmed, (AlQalam Journal of Medical and Applied Sciences, 2026)
The increasing number of networked devices and the limitations of IPv4, such as limited assignable addresses, complex subnetting structure, and inefficient employment of NAT, among others. It is because of these shortcomings of IPv4 that have led to a greater adoption of Internet Protocol version 6 (IPv6) as a scalable and future-ready networking solution. This project outlines the design and execution of a hierarchical IPv6 addressing scheme for a multi-location enterprise network. The design employs a structured subnetting approach, assigning a /48 IPv6 prefix to each site, a /56 prefix to each building, and a /64 prefix to individual subnets. This method ensures efficient use of addresses, scalability, and easier network management. IPv6 Stateless Address Autoconfiguration (SLAAC) is utilized, enabling end devices to dynamically generate their own IPv6 addresses. Additionally, DHCPv6 is incorporated to provide extra network parameters like DNS server information and domain names. This combined approach merges the ease of SLAAC with the administrative oversight provided by DHCPv6. The network architecture is implemented and tested using Cisco Packet Tracer and GNS3 software, featuring multiple routers, switches, and end devices spread across various sites and buildings. IPv6 routing is managed through OSPFv3 to ensure effective and dynamic communication between sites. The findings indicate that the proposed hierarchical IPv6 design improves network scalability, supports efficient address allocation, and facilitates seamless connectivity across different locations. This work underscores the practicality and effectiveness of structured IPv6 subnetting alongside SLAAC and DHCPv6 for contemporary enterprise network setups.